La Enseñanza de las Enfermedades Transmitidas por Alimentos y el desarrollo del Pensamiento Crítico. Aportes desde la Geografía de la Salud (Huellas, 2022)
The review of the doctoral thesis called "The Teaching of Foodborne Diseases (FD) and the development of Critical Thinking. Contributions from the Geography of Health" is presented. In it, the approach to FBDs at different educational levels is presented, as well as an analysis of them from the Geography of Health and the development of didactic sequences in secondary school.